Oblique angle deposition of nickel thin films by high-power impulse magnetron sputtering - Hajihoseini, Hamidreza; Kateb, Movaffaq; Ingvarsson, Snorri Þorgeir; Gudmundsson, Jon Tomas (Beilstein Journal of Nanotechnology, 2019)
Background: Oblique angle deposition is known for yielding the growth of columnar grains that are tilted in the direction of the deposition flux. Using this technique combined with high-power impulse magnetron sputtering (HiPIMS) can induce unique properties in ferromagnetic thin films. Earlier we have explored the properties of polycrystalline and epitaxially deposited permalloy thin films deposited under 35° tilt using HiPIMS and compared it with films deposited by dc magnetron sputtering (dcMS). The films prepared by HiPIMS present lower anisotropy and coercivity fields than films deposited with dcMS. For the epitaxial films dcMS deposition gives biaxial anisotropy while HiPIMS deposition gives a well-defined uniaxial anisotropy.Results: We report on the deposition of 50 nm polycrystalline nickel thin films by dcMS and HiPIMS while the tilt angle with respect to the substrate normal is varied from 0° to 70°. The HiPIMS-deposited films are always denser, with a smoother surface and are magnetically softer than the dcMS-deposited films under the same deposition conditions. The obliquely deposited HiPIMS films are significantly more uniform in terms of thickness. Cross-sectional SEM images reveal that the dcMS-deposited film under 70° tilt angle consists of well-defined inclined nanocolumnar grains while grains of HiPIMS-deposited films are smaller and less tilted. Both deposition methods result in in-plane isotropic magnetic behavior at small tilt angles while larger tilt angles result in uniaxial magnetic anisotropy. The transition tilt angle varies with deposition method and is measured around 35° for dcMS and 60° for HiPIMS.Conclusion: Due to the high discharge current and high ionized flux fraction, the HiPIMS process can suppress the inclined columnar growth induced by oblique angle deposition. Thus, the ferromagnetic thin films obliquely deposited by HiPIMS deposition exhibit different magnetic properties than dcMS-deposited films. The results demonstrate the potential of the HiPIMS process to tailor the material properties for some important technological applications in addition to the ability to fill high aspect ratio trenches and coating on cutting tools with complex geometries.
Keywords: glancing angle deposition (GLAD); high-power impulse magnetron sputtering (HiPIMS); oblique angle deposition; magnetron sputtering; magnetic anisotropy; nickel